Distribuição espacial dos moluscos bivalves na região da plataforma continental do Cabo Frio, Praia de Maçambaba, Estado do Rio de Janeiro, Brasil - Gomes, Abilio Soares (1989)
Molluscs bivalves of the continental shelf of the Cabo Frio region were sampled every month, during September 1985 to February 1987, using a Van-Veen grab, a rectangular dredge and a otter trawl. Forty five species were identified belonging to 29 families. The spatial distribution at 30, 45 and 60 metres of depth was determined by classification and ordination analysis. The distribution paterns were compared with data obtained with dredge and grab, and also with results given by the simple matching índex and by Pearson coefficient of linear correlation. It was possible to verify the existence of two communities: one living between 30 and 45 meters and another at 60 metros. The most frequent species were Mactra petiti Orbigny,1846, Tellina petitiana Orbigny,1846, Tellina gibber Ihering,1907 and Crassinella lunulata(Conrad,1834) at 30m and Nucula puelcba Orbigny,1846, Corbula patagonica Orbigny,1846 and Malletia cumingii (Hanley, 1860) at 60m. The average size of the particles and selection coefficient of the sediment seem to be the main cause of this distribution. The relation trophic group/sediment type hypothesis seems to be applied to the studied area, ocurring higher number of species and organisms with detritivorous habit at 60m and a higher number of species an organisms with .suspensivorous habit at 30 and 45m. The highest values of diversity were verified at 60m, possibly due to a higher spatial heterogeneity and a higher hydrodynamic stability of the sediments at -'this depth. There was no sazonality in the occurrence or density of any species collected.